Efficient GPR data acquisition to detect underground pipes. (October 2017) - Prego, F.J.; Solla, M.; Puente, I.; Arias, P.
Abstract: This work presents the ground penetrating radar as a non-destructive solution to detect buried pipes and minimize the impacts to the services in the intervention area such as leakages in the buried utilities, particularly massive in urban areas. An experimental zone was built including various types and configurations of piping. Different antenna frequencies and parameter setting were tested in order to provide an efficient field data acquisition that guarantees accurate results in detection. For shallower pipes, a 2.3 GHz antenna with 2 cm of trace-interval has provided the best results. However, 1 GHz and 800 MHz data have revealed complementary information when surveying deeper pipes. Highlights: Efficient GPR field data acquisition and parameter settings to detect buried pipes. Experimental study containing different simulated scenes of buried pipes. Analysis of antenna frequency, time window, trace-interval and spatial resolutions. 2.3 GHz frequency for shallower pipes and 1000-800 MHz frequencies for deeper pipes. Parallel antennas orientation is recommended to improve horizontal resolution.